2008
DOI: 10.1007/s11695-008-9473-3
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer After Laparoscopic Adjustable Gastric Banding

Abstract: A 63-year-old woman with BMI 46 underwent laparoscopic gastric banding. In the standardized follow-up after 14 and 24 months, the GI series and gastroscopy showed no pathological signs. The patient had hematemesis 32 months after gastric banding, followed by symptoms of obstruction, for which a laparotomy was performed. At operation, peritoneal carcinomatosis due to gastric cancer was found. Symptoms after bariatric procedures can be similar to symptoms of gastric or esophageal cancer. We believe that yearly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
9
1
1
Order By: Relevance
“…However, complete resolution of diabetes was less than reported in a published meta-analysis [4]. Reasons for this difference may have been the high BMI of our patients and the early onset of diabetes prior to surgery.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, complete resolution of diabetes was less than reported in a published meta-analysis [4]. Reasons for this difference may have been the high BMI of our patients and the early onset of diabetes prior to surgery.…”
Section: Discussioncontrasting
confidence: 57%
“…Two patients died due to their severe comorbidities 6 months and 96 months after GB. One patient died due to gastric cancer 36 months after GB [4]. Another woman died after repair of an abdominal wall hernia 132 months after band implantation.…”
Section: Resultsmentioning
confidence: 99%
“…In the available literature, no cases similar to the presented one was found. Cancer occurrence after band placement was described, but it appeared above the band [10] or in the area where it was applied, and it was connected with its migration [9]. Risk factors which might have influenced the development of cancer in our patient are female sex and obesity lasting since childhood.…”
Section: Discussionmentioning
confidence: 92%
“…Nine studies reported data on preoperative upper endoscopy; in 4 of them [14], [17], [22], [28], a preoperative endoscopy had not been performed, and in 5 studies, a preoperative endoscopy had been performed [7], [9], [13], [20], [27]. Among these studies, there was 1 normal endoscopic appearance [13], 1 patient with gastric pouch ulcerations [7], 1 patient with intestinal metaplasia in the stomach [27], and 2 patients with Barrett's esophagus [9], [20]. In the latter 2, an adenocarcinoma of the esophagogastric junction developed 21 years [9] and 5 years [20] later.…”
mentioning
confidence: 99%